REDEFINING THE MEANING OF ASY-SYIFA’ IN THE QUR’AN AS QUR’ANIC HEALING IN PHYSICAL AILMENTS - Hidayah, Aida; Firdausi, Fitriana (Jurnal Studi Ilmu-ilmu Al-Qur’an dan Hadis, 2021)
In the historical record of Islam, even in the early era of the formation of Islam, the practice of treating the Koran or certain units of the Koran into something meaningful in the practical life of the people has basically occurred. The history of Islam also records the existence of the phenomenon of treating physical ailments by reciting the holy verses of the Koran, for example the al-Fatihah which was read by a companion of the prophet which can remove the effects of poisonous stings. This phenomenon continues and is widely practiced by Muslims. However, not a few consider it an act of shirk because it treats the verses of the Koran as inappropriate for their function and is considered influenced by other cultures that are contrary to Islamic rules. that notion is based on the meaning of the word Asy-Syifa’ in the Qur’an which tends to specialize in the meaning of spiritual healing. This article attempts to review the concept of asy-Syifa” in the Qur’an, especially in relation to the use of Qur’anic verses as a method of treating physical ailments. This research is a library research using the theory of Kamaruddin Hidayat concerning the steps of interpretation, namely using the verses of the Koran as a source of interpretation, adding information from the hadith of the prophet and paying attention to the community environment when the Qur’an was revealed and the use of a word used in that community. The results of this research reveal that the word asy-Syifa” in the Koran can also mean a cure or medicine for all kinds of diseases, both mental and physical ailments. Keywords: Al-Qur’an, asy-Syifa’, treatment of physical ailments